Medico-legal aspect of maternal death. - N. Kuralkar, Ravindra; A. Devraj, Nilesh; B. Buchade, Dhiraj (International Journal of Research in Medical Sciences, 2017)
Background: With the increasing numbers legal suits against the practicing doctors now a day, it’s important to addressed sudden and unexpected death of young female during pregnancy or birth which leads to severe strain and anguish to family members. If this is not adequately resolved, healing cannot occur. It is then that the family may pursue the legal process to help obtain answers about what happened and, more importantly, why it happened to their loved one. Methods: Total 95 cases of maternal deaths which were brought for postmortem were studied during period of August 2012 to July 2014. Results: Maximum cases of deaths occurs after normal delivery 44 (46.3%) and deaths in hospital were 72 (75.8%). In 7 (7.4%) cases death was occurred during transport to medical facility. Post-partum hemorrhage remains the leading cause followed by sepsis 13 (13.7%) in direct causes of maternal deaths. Conclusions: The present study was carried out with view to determine various factors and causes of maternal deaths, utility of medicolegal autopsy and autopsy record as a useful and adjunct data source for ascertainment of maternal deaths and elucidating the emerging trends. Some special cases are discussed with the help of medicolegal knowledge, which point out fallacies while treating these cases such as proper use drugs, surgical procedures while dealing with cases of abortion and ectopic gestation, sterilization operations etc.